2001
DOI: 10.1097/00000637-200109000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Findings in Reexcision of Incompletely Excised Basal Cell Carcinomas

Abstract: In common practice, patients with incompletely excised basal cell carcinomas (BCCs) are referred to elective reexcision. In previous reports, it was observed that tumor cells are found in only 50% of the reexcised specimens. The authors performed a retrospective analysis of a large series of patients to evaluate clinical and pathological findings in patients who underwent reexcision of incompletely excised BCCs. A total of 1,478 BCCs arising in 1,278 patients were excised by plastic surgeons in a plastic and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 7 publications
5
20
2
2
Order By: Relevance
“…Residual tumour was found in only just over half the specimens excised further. This number is virtually identical to that reported by Griffiths [1], whereas other series reported even lower values of about 30% [7,10]. Although the other reports were not specific for BCC of the nose, these findings raise the question of the therapeutic attitude in such cases.…”
Section: Discussionsupporting
confidence: 87%
“…Residual tumour was found in only just over half the specimens excised further. This number is virtually identical to that reported by Griffiths [1], whereas other series reported even lower values of about 30% [7,10]. Although the other reports were not specific for BCC of the nose, these findings raise the question of the therapeutic attitude in such cases.…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies we have described risk factors associated with incomplete excision of basal cell carcinomas (5,6). Our results were among several other publications that described incomplete excision of basal cell carcinomas (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22); however, only a few studies were published on risk factors that may play a role in incomplete excision of SCCs (1)(2)(3)(4).…”
Section: Introductionsupporting
confidence: 64%
“…In the past, most of the studies of surgical clearance rate pertained to basal cell carcinomas, with surgical failure rates between 4% and 16% (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Only a few studies reported on surgical failure rates in SCCs that range between 0% and 16% (1-4).…”
Section: Discussionmentioning
confidence: 99%
“…The chin (20 percent), periorbital (17.9 percent) and periauricular regions (17 percent), and forehead and tem- 12,19,23 The percentage of incomplete excision for morpheic basal cell carcinomas was significantly higher than all other subtypes. This finding has been confirmed in several studies.…”
Section: Discussionmentioning
confidence: 96%